2019
DOI: 10.4103/ijo.ijo_568_18
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine levels in human tear fluid

Abstract: Purpose:To determine the levels of dopamine in tear fluid and demonstrate the use of tear fluid as a non-invasive source for dopamine measurements in humans.Methods:The study cohort included 30 clinically healthy individuals without any pre-existing ocular or systemic conditions. Matched tear fluid (using Schirmer's strips and capillary tubes) and plasma were collected from the subjects. Dopamine levels were evaluated using direct competitive chemiluminescent enzyme-linked immunosorbent assay (ELISA), dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The concentration of DA in the tear samples was estimated from this calibration plot by mapping the observed current response to the specific concentration. The DA levels in the collected tear samples varied between 4 and 7 nM, which is in good agreement with typical DA levels found in healthy individuals …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The concentration of DA in the tear samples was estimated from this calibration plot by mapping the observed current response to the specific concentration. The DA levels in the collected tear samples varied between 4 and 7 nM, which is in good agreement with typical DA levels found in healthy individuals …”
Section: Resultssupporting
confidence: 86%
“…The DA levels in the collected tear samples varied between 4 and 7 nM, which is in good agreement with typical DA levels found in healthy individuals. 56 An additional step was taken to confirm and validate the DA concentration in the tear samples. This verification was achieved by measuring the DA level in the collected tear samples using liquid chromatography-tandem mass spectrometry (LC−MS/MS) with MRM, a highly precise analytical technique commonly employed for the identification and quantification of various compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is also essential to consider that a single sampling method may not be ideal for all scenarios. Side-by-side comparisons have shown that Schirmer strips collect more proteins than glass capillary tubes 156,157 , glass capillary tubes collect more metabolites than Schirmer strips 89,158 , Schirmer strips and glass capillaries offer comparable coverage of the tear uid lipidome 89 , and polytetra uoroethylene tubes collect signi cantly higher amount of lipids, such as wax esters (p < 0.04) and cholesterol esters (p < 0.04), than glass capillary tubes 159 . Therefore, careful consideration must be taken when comparing the results of studies using Schirmer strips to studies using microcapillary collection 156 .…”
Section: Pitfalls and Challengesmentioning
confidence: 99%
“…Thereby, μPAD and ELISA are the effective methods to quantify tear lactoferrin in DED patients [209]. Another study found that tear dopamine was higher than in plasma dopamine, which suggested that tear fluid be a noninvasive source to monitor dopamine changes [217].…”
Section: Elisamentioning
confidence: 99%